2003
DOI: 10.1074/jbc.m300825200
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Primary Structure Elements Controlling Early Amyloid β-Protein Oligomerization

Abstract: Assembly of monomeric amyloid ␤-protein (A␤) into oligomeric structures is an important pathogenetic feature of Alzheimer's disease. The oligomer size distributions of aggregate-free, low molecular weight A␤40 and A␤42 can be assessed quantitatively using the technique of photo-induced cross-linking of unmodified proteins. This approach revealed that low molecular weight A␤40 is a mixture of monomer, dimer, trimer, and tetramer, in rapid equilibrium, whereas low molecular weight A␤42 preferentially exists as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

47
359
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(406 citation statements)
references
References 63 publications
47
359
0
Order By: Relevance
“…Substitution of Ile-41 by Gly, eliminating both the side chain and the stereocenter of the C R group, yielded a distribution that was qualitatively similar to that of A -(1-40) ( Figure 4B). 36 When Ile-41 was substituted by Ala, the oligomer size distribution was a composite of the distributions characteristic of A (1-40) and A (1-42) ( Figure 4B), whereas substitution of Ile-41 by Val or Leu yielded distributions that were similar to WT A (1-42) in the amount of paranuclei formed but displayed substantially fewer high order oligomers. 36 These data indicated that a minimal alkyl side-chain in position 41, such as the methyl group of Ala, was essential for paranucleus formation.…”
Section: Picup As a Tool For Structural Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Substitution of Ile-41 by Gly, eliminating both the side chain and the stereocenter of the C R group, yielded a distribution that was qualitatively similar to that of A -(1-40) ( Figure 4B). 36 When Ile-41 was substituted by Ala, the oligomer size distribution was a composite of the distributions characteristic of A (1-40) and A (1-42) ( Figure 4B), whereas substitution of Ile-41 by Val or Leu yielded distributions that were similar to WT A (1-42) in the amount of paranuclei formed but displayed substantially fewer high order oligomers. 36 These data indicated that a minimal alkyl side-chain in position 41, such as the methyl group of Ala, was essential for paranucleus formation.…”
Section: Picup As a Tool For Structural Studiesmentioning
confidence: 98%
“…36 When Ile-41 was substituted by Ala, the oligomer size distribution was a composite of the distributions characteristic of A (1-40) and A (1-42) ( Figure 4B), whereas substitution of Ile-41 by Val or Leu yielded distributions that were similar to WT A (1-42) in the amount of paranuclei formed but displayed substantially fewer high order oligomers. 36 These data indicated that a minimal alkyl side-chain in position 41, such as the methyl group of Ala, was essential for paranucleus formation. Moreover, whereas the propyl and iso-butyl side chains of Val and Leu, respectively, supported paranucleus formation, the sec-butyl side chain of Ile-41 was important for paranucleus self-association ( Figure 4B).…”
Section: Picup As a Tool For Structural Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…During PICUP coupled with sizeexclusion chromatography, A␤40 and A␤42 display distinct oligomer size distributions: A␤40 displays a rapid equilibrium among monomers, dimers, trimers, and tetramers, whereas A␤42 preferentially forms pentamer͞hexamer units (paranuclei), which further assemble into beaded superstructures similar to early protofibrils (15). Additional studies of primary structure elements controlling early oligomerization demonstrate that Ile-41 is critical for paranucleus formation by A␤42 and that Ala-42 is necessary for further assembly of A␤42 into larger oligomers (16). In addition, oxidation of Met-35 blocks paranucleus formation but does not alter the A␤40 oligomer size distribution (17).…”
mentioning
confidence: 99%